Staphylococcal Protein A Promotes Colonization and Immune Evasion of the Epidemic Healthcare-Associated MRSA ST239 - Hong, Xufen; Qin, Juanxiu; Li, Tianming; Dai, Yingxin; Wang, Yanan; Liu, Qian; He, Lei; Lu, Huiying; Gao, Qianqian; Lin, Yong; Li, Min (Frontiers in Microbiology, 2016)
The highly successful epidemic of healthcare-associated methicillin-resistant Staphylococcus aureus (HA-MRSA) ST239 is a growing concern worldwide, due to its progressive adaptation to the highly selective environment of the healthcare system. HA-MRSA ST239 display the reduced virulence and successfully colonize in hospital settings, while the emergent community-associated MRSA (CA-MRSA) maintain full virulence and cause infections in the community environment. Our aim was to investigate what enables S. aureus ST239 to be highly adaptive under hospital circumstances and gradually progress to a series of widespread invasive infections. We found that spa expression of HA-MRSA ST239 is much higher than that of CA-SA ST398. And we discovered that the highly production of staphylococcal protein A (SpA), having no concern with spa gene structure, enhances nasal colonization and cell adhesion in ST239. S. aureus ST239 defends against the adaptive immune response by resisting phagocytosis and inducing apoptosis of B cells through expression of surface-anchored and released protein A, facilitating its dissemination within the circulatory system to other organs. Protein A also plays another key role in subverting the host immune response through its ability to induce early shedding of TNF-α receptor 1 (TNFR1) from phagocytic cells. The increased levels of soluble TNFR1 present during experimental S. aureus ST239 infection may neutralize circulating TNF-α and impair the host inflammatory response. Protein A is also a virulence factor, as tested in our bacteremia model in mice, contributing to the durative tissue damage of abscess formation sites in ST239 infection. These functions of protein A eventually benefit to widespread infections of S. aureus ST239. We draw the conclusion that Staphylococcal Protein A may be a crucial determinant in the colonization and immune evasion of ST239 infections, contributing to persistent spread in the hospital settings. These results suggest that antibodies against protein A may provide insights into the development of novel treatments against S. aureus, especially HA-MRSA.